Perception of Participants towards Prevention and Control HIV/AIDS: A Qualitative Study - Bhandari, Khimananda; Giri , Surendra (Kaladarpan कलादर्पण, 2025)
This qualitative study explores the perceptions and experiences of People Living with HIV/AIDS (PLHA) in Rupandehi, Nepal, focusing on awareness, stigma, and preventive strategies. Using a qualitative approach, data were collected from 40 respondents through Focus Group Discussions (FGDs) at four VCT centers. The findings reveal a significant shift in perceptions, with most participants demonstrating awareness of symptoms, transmission modes, and prevention methods, attributed to counseling and medical advancements. However, stigma and discrimination persist, especially among women, with negative attitudes from families, communities, and even healthcare providers. Socio-economic challenges, including migration, poor living conditions, and limited resources, were identified as critical factors contributing to vulnerability. Despite these challenges, respondents believed that HIV/AIDS prevention is possible through education, economic stability, healthcare access, and societal support. The study underscores the need for holistic interventions addressing structural inequalities, reducing stigma, and empowering PLHA to foster prevention and improved quality of life.